The Influence of Team Games Tournament Model on Learning Motivation through Students' Learning Interest - Damayanti, Sinta; Hariani, Lilik Sri; Naim, Naim (IJBLE Scientific Publications Community Inc., 2025)
This study aims to determine the effect of the Team Games Tournament (TGT) learning model on student motivation through learning interest as a mediating variable. The approach used is quantitative with regression and path analysis methods. The results showed that the TGT model had an effect on learning interest and motivation, and learning interest played a mediating role in the relationship. This study illustrates that a fun and collaborative learning strategy such as TGT can increase students' engagement and enthusiasm for learning. It is hoped that the results of this study can be a reference in the application of learning models that encourage students' affective aspects optimally